Implementasi Kurikulum Merdeka dalam Pembelajaran PAI di SMPN 07 Kota Cimahi - In In Inayatillah; Muhammad Zahran As Shidiq; Nita Ramadhani; Umar Rosadi (Jurnal Dirosah Islamiyah, 2025)
The implementation of the Merdeka Curriculum in educational units emphasizes freedom and flexibility in learning, for both teachers and students. This research is motivated by the phenomenon that the implementation of the Merdeka curriculum in schools has not been optimal. The indicators of this suboptimality include: teacher readiness in implementing the Merdeka curriculum, limited learning time for optimal implementation of the Merdeka curriculum, and lack of critical thinking skills in students. The purpose of this study is to determine the implementation of the Merdeka curriculum in the SMPN 07 CIMAHI CITY environment and analyze its impact on students' understanding of Islamic values. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. The results show that the implementation of the Merdeka curriculum at SMPN 07 CIMAHI has gone well, this can be seen from student learning outcomes. However, there are still several obstacles, one of which is the lack of classroom facilities.